Muslim Consumer Behavior Toward Green Financing and Eco-Friendly Products in Islamic Economic Perspective - Anisa Marseli; Hariyanti Hariyanti; Khusniddinov Oloviddin (International Forum of Researchers and Lecturers, 2024)
This study explores the impact of religious values on Muslim consumers' behavior toward green financing and eco-friendly products within the framework of Islamic economics. The research utilized a quantitative approach with a descriptive survey method, surveying 250 Muslim consumers from urban areas in Indonesia. A structured questionnaire with a five-point Likert scale was employed to measure religiosity and eco-friendly purchasing behavior. The multiple regression analysis showed that religiosity significantly influences green purchasing behavior, with higher religiosity scores correlating with greater engagement in environmentally conscious purchasing decisions. Additionally, the t-test and ANOVA revealed significant differences between Sharia-compliant and non-Sharia-compliant groups, with the Sharia-compliant group exhibiting stronger eco-friendly purchasing behavior. These findings suggest that Islamic principles related to environmental stewardship, such as Khalifa (guardianship of the earth) and Israf (avoiding wastefulness), play a significant role in shaping consumer attitudes toward sustainability. The study concludes that religious values are a crucial determinant of green purchasing behavior and that incorporating these values into sustainability initiatives can effectively promote eco-friendly behavior, especially in communities where religion plays a central role. Policymakers and educators can leverage religious frameworks to foster sustainability and encourage more responsible consumer behavior in Muslim-majority communities.